SISTEM KEAMANAN KEBOCORAN GAS BERBASIS INTERNET OF THINGS DENGAN FITUR PEMADAMAN KOMPOR OTOMATIS - Anggun Imelda; A. Rahman; Muhammad Amri Yahya (Teknik Elektro Polsri, 2025)
LPG (Liquefied Petroleum Gas) leakage is a major problem that has the potential to trigger fires and explosions. An Internet of Things (IoT)-based security system offers an innovative solution to detect and prevent gas leaks by sending automatic notifications and providing responses. In this study, MQ-6 gas sensors along with fan actuators and circuit breaker relays are used in the gas leak detection system. The level of leakage and ambient temperature are used in the fuzzy logic decision-making process. Fan activation, and WhatsApp notifications are the results. The system was tested to ensure that the leak detection and automatic response were successful. The test results showed that the system has the ability to handle leaks quickly and accurately.